Gender disparities and risk factors in infant mortality in Indonesia - Wardani, Yuniar; Djannah, Sitti Nur; Santri, Ichtiarini Nurullita (Jurnal Cakrawala Promkes, 2024)
The Infant Mortality Rate (IMR) is closely related to the Human Development Index (HDI), which measures a country's social and economic development. The decline in IMR based on gender is thought to be related to discrimination in the treatment of female babies, unequal nutritional needs of female babies, and utilization of health service facilities. This study aims to investigate the relationship between risk factors and infant mortality with gender stratification. Using a cross-sectional approach based on secondary data from the 2012 and 2017 Indonesian Demographic and Health Survey (IDHS), the research sample consisted of women of childbearing age (15-49 years) who had given birth, totaling 3694 and 3413 women in 2012 and 2017, respectively. Data analysis was conducted using logistic regression and the sampling technique employed was two-stage stratified random sampling. From the 2012 and 2017 IDHS, variables influencing infant mortality based on gender included maternal age (0.23 95% CI 0.14-0.37; 3.17 95% CI 1.94-5.17), parity (0.49 95% CI 0.33-0.72; 2.53 95% CI 1.75-3.68), place of birth (0.47 95% CI 0.33-0.67; 0.61 95% CI 0.41-0.89), and body weight (2.67 95%CI 1.75-4.08; 3.31 95% CI 2.12-5.17). Baby girls with small birth weights were at higher risk of dying compared to baby boys, while male babies born to older mothers were at greater risk of death compared to female babies. Antenatal care is an essential key in reducing various risks of infant death based on gender, playing a crucial role in ensuring healthier outcomes for both male and female infants through early detection and targeted interventions.